Gross Anatomy of Humerus of Asiatic Lion (Panthera leo persica) - Pandya, Sweta; Gaikwad, Pradnya; Patel, Maitri (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Gir forest is the sole home of Asiatic lion. In the present study the anatomy of 4 humerus bones of Asiatic lion were studied. The humerus is long bone with spirally twisted shaft. The mean circumference of proximal extremity was 21.11 cm, while that of distal extremity was 18.00 cm. The mean length of shaft was 17.20 cm. The mean diameter of shaft from the middle was 8.62 cm. The musculo-spiral groove was wide, smooth and spiral on lateral surface of humerus. There were three fossae, olecranon fossa at caudal aspect and radial and coronoid fossae at cranial aspect of distal extremity of humerus. Supracondyloid foramen was present on medial side of distal extremity above medial condyle.
Keywords: Humerus; Lion; Morphology; Morphometry